The historical development of the housing policy of Russian cities from pre-industrialization period to free real estate market. (1st November 2020) - Siegmunt, Olga
ABSTRACT: This article focuses on long-term housing policy in Russia (1917 onwards). In view of the fact that during the Soviet era housing policy was set by the head of state, the article will discuss the following four periods: pre-industrialization, from industrialization to the Stalin era, from the Khrushchev era to developed Socialism, and post-Soviet collapse. The historical analysis of Soviet housing policy begins with the pre-industrialization period when significant political decisions were taken. A systematic and chronological description of normative legal documents then introduces the reader to the topic and gives a basic knowledge of the physical and social structure of the society. In the next part of this article, the main tendencies in housing policy up until the beginning of the 1950s are then described. Both the pre-industrial period and the period into the 1950s constitute the characteristics of a housing policy that was sustained until the end of the Soviet period.